International Law Against Countries That Have Introduced Sanctions Pollution - Nasir Sitompul, Mhd (International Asia Of Law and Money Laundering, 2023)
The 1982 International Convention on the law of the sea or UNCLOS describes the rules, actions, and uses of the sea nationally and/or internationally. Pollution activities arise from various sectors and polluters not only the state but the existence of corporations is also able to trigger the emergence of pollution, especially in the field of waters that will seep through the flow of water and also follow the wind wave (wind wave) to enter the territory of another country. Research conducted is normative legal research or doctoral research, based on the results of research that the settlement of international sea zinc has been described in the International Convention on Article 287 paragraph (1) Chapter XV UNCLOS 1982 on the selection of Settlement Procedures. In fact sanski that has been given is not implemented because the sanctioned countries do not put forward the principle of good faith.